Pengaruh Model Pembelajaran Kooperatif Tipe NHT (Numbered Heads Together) dan Kemampuan Awal Terhadap Hasil Belajar Siswa pada Mata Pelajaran Fisika Di SMP Negeri 2 Poso - Abd. Rasyid; Marungkil Pasaribu; H. Kamaluddin (Universitas Tadulako, 2015)
This education research aims to investigate the difference learning outcomes of the students taught using cooperative learning model NHT type and conventional type on physics subject of SMP Negeri 2 Poso, find out the different result of students with high beginning ability and those have low ability on physics, and find out whether any or not interaction of learning model and beginning ability of the students learning outcomes on physics. The Population was 130 students of the eighth grade. The research sample consisting of class VIIIA and VIIIB. Design used was factorial 2 x 2. The data were collected through thinking ability and learning achievement test. The data were analyzed by using ANOVA two ways. The result indicates that there was difference of learning outcomes of students taught cooperative learning NHT type from those taught conventional method (p-value < 0,05), different learning outcomes of the students with high beginning ability and those with low beginning ability (p-value < 0,05), no interaction between learning model and beginning ability toward the students learning outcomes (p-value > 0,05) that means the students with high beginning ability will be better their learning outcomes than those with low beginning ability of cooperative learning model NHT type or conventional learning